Economic Duress and its Effect to the Contract under English and Iraqi Law - علي كاظم كريم (Journal of Legal Sciences, 2019)
English law, unlike many Anglo-Saxon laws, has adopted the doctrine of economic duress delayed. Under this doctrine, the contractor who has entered into a contract as a result of an unlawful pressure that threatens his financial or commercial interests may rescind the contract on the grounds that the contract was concluded under economic duress which make the contact voidable. More than forty years have passed since the adoption the economic duress doctrine in English law, however, there are still some issues remain controversial. Is the Lawful Act duress economic duress? Iraqi Civil Law did not explicitly regulate the doctrine of economic duress. However, the Iraqi authors when explain the rules of duress under this law indicate that these rules can cover the subject of “contracting in case of necessity” and considered the contact in this case is suspended. Moreover, they considered that using legitimate means to reach an illegal destination is one types of duress under Iraqi Civil Law types. Hence, in my opinion there is no gap in Iraqi law in the subject.